Pertumbuhan Dan Perkembangan Anggrek Dendrobium anosmum Pada Media Kultur In Vitro Dengan Beberapa Konsentrasi Air Kelapa - S. Tuhuteru; Meity L Hehanussa; Simon H.T Raharjo (Agrologia, 2012)
Dendrobium anosmum is one of natural orchids in Indonesia. Optimization of medium composition for orchid propagation through in vitro culture is necessary to enhance propagule multiplication capabilities and quality. This study was aimed to study the influence of concentration of coconut water in culture medium on in vitro growth and development of D. anosmum orchid species and to determine the optimal coconut water concentration in culture media.  The experiment were arranged in a Completely Randomized Design with four treatments and eight replications. The treatments consisted of the addition of coconut water with concentrations: 0 ml•l -1 (control), 50 ml•l-1, 100 ml•l-1 and 150 ml•l-1. The results showed that addition of coconut water in culture medium gave different effect on shoot growth and multiplication of D. anosmum orchids.  Coconut water concentration of 100 ml•l-1 was the best concentration for growth and multiplication of D. anosmum orchids, based on both shoots and roots growth, plantlet height and wet weight.